مشكلة اللاجئين الفلسطينيين: بين التحدي الصهيوني والاستجابة العربية - فاتح, شيباني (University of Eloued جامعة الوادي, 2020)
رت قضية اللاجئينالفلسطينيينبعد نتائجحرب1948،حيث هاجرالآلافمنهم جراء هذه الحرب وقد كانت دول الجوار أهم مأوى وملجأ إليهم بحكم الجغرافيا،إلا أنها تحولت إلى مشكلة بعد اتفاقيات الهدنة التي عقدتها هذه الدولمع الكيان الصهيوني،بحيثكانت هذه الاتفاقياتبمثابة اعتراف ضمنيلإسرائيلفي العيشبأمان في المنطقة العربية وهي فيالوقتنفسه.بمثابةالخطوة الأولى للتخلي عن حقوق اللاجئين الفلسطينيين في العودة إلى ديارهم،وقد ازدادت الأمور تعقيدا وتأزما وفقدانا لأمل العودة بعد نتائج حرب جوان1967وما خلفته من توسع على حساب هذه الدول نفسهاـفالتحدي الصهيوني منذ قرار تقسيم فلسطين سنة1947لم يلق أي استجابة عربية فعالة بخصوص تحرير فلسطين وعودة اللاجئين الفلسطينيين إلى أرضهم أرض فلسطين.وإنما سعى بالدرجة الأولى إلى محاولة تحرير أراضيها وإزالة آثار حرب1967 The issue of the Palestinian displacement appeared as a result of the 1948 War, where thousands of Palestinians migrated, mainly, to neighboring countries that became the most important refuge due to geographical reasons. However, the armistice agreements that these countries concluded with the Zionist entity complicated the refugees’ situation since these agreements were tacit recognition of Israel and a guarantee of a safe living in the Arab region. These agreements were the first step of giving up on the rights of the Palestinian refugees to return to their homes. Matters aggravated and became more complicated, and the hope of returning home was lost after the results of the June War 1967 and the resultant expansion at the expense of these countries. Since the partition of Palestine in 1947, the Zionist challenge did not receive any effective response from Arab countries regarding the liberation of Palestine and the Palestinian refugees’ return 11511011141292020 to their land; in fact, Arab countries’ response sought, primarily, liberating their own territory and wiping the effects of the 1967war.
مجلد11، عدد1
Keywords: سطين؛اللاجئون؛العودة؛الدول العربية؛التحدي؛الإستجابة.; Palestine; Refugees; Return; Arab Countries; Challenge; Response